Phosphate glass fibers facilitate proliferation and osteogenesis through Runx2 transcription in murine osteoblastic cells - Lin, Xiao; Chen, Qiang; Xiao, Yunyun; Gao, Yongguang; Ahmed, Ifty; Li, Meng; Li, Hui; Zhang, Kewen; Qiu, Wuxia; Liu, Xianhu; Boccaccini, Aldo R.; Qian, Airong (Journal of Biomedical Materials Research Part A, 2019)
Cell-material interactions and compatibility are important aspects of bioactive materials for bone tissue engineering. Phosphate glass fiber (PGF) is an attractive inorganic filler with fibrous structure and tunable composition, which has been widely investigated as a bioactive filler for bone repair applications. However, the interaction of osteoblasts with PGFs has not been widely investigated to elucidate the osteogenic mechanism of PGFs. In this study, different concentrations of short PGFs with interlaced oriented topography were cocultured with MC3T3-E1 cells for different periods, and the synergistic effects of fiber topography and ionic product of PGFs on osteoblast responses including cell adhesion, spreading, proliferation, and osteogenic differentiation were investigated. It was found that osteoblasts were more prone to adhere on PGFs through Vinculin protein, leading to enhanced cell proliferation with polygonal cell shape and spreading cellular actin filaments. In addition, osteoblasts incubated on PGF meshes showed enhanced alkaline phosphatase activity, extracellular matrix mineralization, and increased expression of osteogenesis-related marker genes, which could be attributed to the Wnt/beta-catenin/Runx2 signaling pathway. This study elucidated the possible mechanism of PGF on triggering specific osteoblast behavior, which would be highly beneficial for designing PGF-based bone graft substitutes with excellent osteogenic functions.
CRIS-Team WoS Importer:2019-11-15